자주식 배추수확기의 인발성능 및 전처리부 설계 - 김호진; 최영수; Ho-Jin Kim; Yeong-Soo Choi (농업생명과학연구, 2020)
본 연구에서는 주행부, 주반송부, 동력전달부 등으로 구성된 배추를 인발하여 수확할 수 있는 궤도형의 자주식 인발형 배추수확기 개발, 인발기능과 이송기능을 갖는 주이송부의 설계 요인에 따른 포장 수확 성능 평가, 우리나라 품종별 재배작형에 따른 배추 물리적 특성 분석 및 시작기의 인발 및 반송 성능 향상을 위한 전처리부 설계를 수행하였다. 수확기 설계를 위한 기초 자료로 활용하기 위해서 우리나라 계절별 대표 품종(봄배추: 대통배추, 가을배추: 노랑배추, 월동배추: 겨울왕국)에 대해 수확시기의 물리적 특성을 조사하였다. 겉잎을 제거하지 않은 상태에서 크기를 품종별 평균값으로 나타냈을 때 3가지 품종에 있어서 폭은 22.7 ~ 30.6 cm, 높이 29.9 ~ 33.8 cm 범위로 나타났으며, 수직인발력은 평균 90.8~159.5 N으로 다양하게 나타났다. 인발각도, 속도비를 인발성능 요인으로 고려한 인발성능 평가에서 인발각도 35°, 수확기 주행 속도가 0.4 m/s 이고 인발벨트 속도 0.61 m/s 일 때의 속도비 1 : 1.22에서 인발률 80%로 인발정도가 가장 높게 나타났으나, 보다 향상된 배추 인발성능을 확보하기 위해서는 인발 시 배추를 안정적으로 전달할 수 있는 메카니즘이 추가로 요구되어 배추수확기 주이송부의 전방에 부착할 수 있는 유인부와 보조반송부로 구성된 전처리부를 전장 88 cm, 전폭 60 cm, 전고 15 cm의 치수로 설계･제시하였다. This research was conducted to evaluate the pulling performance of a Chinese cabbage harvester, which was designed and constructed for a self-propelled harvester with pulling mechanism. The harvester is consisted of crawler-type running gear, main pulling conveyor, hydro static transmission system as main units. In order to get the informations for developing a pulling mechanism, physical properties of three types of Chinese cabbages, which were cultivated in different seasons of spring, autumn and winter, were investigated. Also, vertical pulling force was measured. The size of the three types of Chinese cabbages ranged from 22.7 cm to 30.6 cm in width and 29.9 cm to 33.8 cm in height. In general, winter Chinese cabbage showed larger size than other varieties. The pulling force ranged from 90.8 N to 159.5 N on average. Field tests were carried out to evaluate the pulling performance of the harvester. The results of the test showed the best pulling rate of 80% when the conditions were at inclined angle of 35° of the main conveyor, the driving speed of 0.4 m/s, and the belt speed of 0.61 m/s (speed ratio 1:1.22). However, the results suggested that an auxiliary device such as a preprocessing unit should be designed to enhance the pulling and conveying performance. The preprocessing unit was designed so that it can be attached in front of the main pulling conveyor of the prototype harvester and is consisted of induced unit and auxiliary pulling conveyor. The preprocessing unit was designed with dimensions of 88 cm in overall length, 60 cm in overall width and 15 cm in overall height. It is expected that the unit can help for Chinese cabbages to be pulled out easily and to ensure stable transfer along the main pulling conveyor.